An elementary approach to containment relations between symbolic and ordinary powers of certain monomial ideals. Issue 11 (2nd November 2017) - Keane, Ryan W.; Küronya, Alex; McMahon, Elise
ABSTRACT: We provide an elementary explanation of a surprising result of Ein–Lazarsfeld–Smith and Hochster–Huneke on the containment between symbolic and ordinary powers of ideals for a certain class of simple monomial ideals.